Molecular characterization of virulent genotype XIII Newcastle disease virus isolates from desi-chickens in Namakkal, South India - D. Malar; P. Ponnusamy; S. Saravanan; M. Sasikala; K. Sukumar (Veterinary Research Communications, 2026)

Haplotype-based multi-locus genome-wide association study reveals genomic regions associated with reproductive stage high temperature stress tolerance in rice - Adhip Das; Madan Pal; Adam H. Price; Sukumar Taria; Ayushman Mallick; Megha Sharma; Sudhir Kumar; Ranjith Kumar Ellur; S. Gopala Krishnan; Lekshmy Sathee; Pradeep Kumar Jain; Monika Dalal; et al. (Plant Molecular Biology, 2026)

Maternal nutrition and metabolic adaptations for healthy pregnancy and fetal programming - N.V. Kanimozhi; Chinta Suneetha; L. Sonali; M.P. Drisya Raj; R. Pavithra; B. Roopa Shri; S. Ashok Kumar; R. Palpandi Raja; M. Sukumar (Food and Humanity, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Mapping of the QTLs governing stem-specific weight for stem reserve mobilisation in wheat (Triticum aestivum L.) under combined heat and drought stress - Sukumar Taria; Ajay Arora; Hari Krishna; Karthik Kumar Manjunath; Sudhir Kumar; Biswabiplab Singh; Shashi Meena; Animireddy China Malakondaiah; S. Kousalya; Jasdeep Chatrath Padaria; Pradeep Kumar Singh; Badre Alam; et al. (Plant Physiology Reports, 2025)

Multivariate analysis and genome wide association mapping for chlorophyll fluorescence and grain number per panicle under high temperature stress in rice - Adhip Das; Madan Pal; Sukumar Taria; Ranjith Kumar Ellur; Sudhir Kumar; Lekshmy Sathee; S. Gopala Krishnan; Monika Dalal; Pradeep Kumar Jain; Viswanathan Chinnusamy (Plant Physiology Reports, 2024)

Photosynthesis and radiation use efficiency at anthesis in relation to biomass accumulation and yield in Basmati rice (Oryza sativa L.) - Payal Priyadarsini; Madan Pal; Rakesh Pandey; S. Gopalakrishnan; Vinay Kumar Sehgal; Viswanathan Chinnusamy; Sukumar Taria; Pramod Kumar; Jasdeep Padaria; Milan Kumar Lal (Plant Physiology Reports, 2024)

Diagnostic Performances of ADC Value in Diffusion-Weighted MR Imaging for Differential Diagnosis of Breast Lesions in 1.5 T: A Systematic Review and Meta-analysis - Winniecia Dkhar; Rajagopal Kadavigere; Suresh Sukumar; Abhimanyu Pradhan; S Sharath (Journal of Medical and Biological Engineering, 2023)
Purpose Medical technology has gone a long way in diagnosis and characterization of breast tumors. Diffusion-weighted MR imaging is the state of the art for breast screening and diagnosing. The aim of this meta-analysis is to evaluate the diagnostic performances of diffusion-weighted MR imaging in characterization of breast lesions with different b value in 1.5 T MRI. Method An extensive search on Scopus, Embase, and PubMed databases were performed on studies published between January 2000 and 2020. The systematic seek initially yielded 2467 studies, out of which 27 research were covered on this meta-evaluation. The included studies for meta-analysis utilized different b value and noted that the ADC value was highly influenced by the b value, for differential diagnosis of breast tumors. Results The current meta-analysis has shown the ADC values was lower for malignant breast lesions as compared with benign lesions. The recommended mean threshold ADC was 1.25 ± 0.17 × 10 –3 mm 2 /s range from 0.93 to 1.60 × 10 –3 mm 2 /s for differential diagnosis of breast tumors. Sub-group analysis on the bases of b value showed statistically significant differences in the ADC value of benign and malignant breast tumors. Conclusion In conclusion, we noted that b value has a significant effect in calculating the ADC value of the breast lesions as well as ADC threshold value but lacks standardization. The ADC value measurement has a potential for differentiation between benign and malignant breast lesions.

Characterization of infectious laryngotracheitis virus isolates from laying hens during 2019–2020 outbreaks in Tamil Nadu, India - P. Ponnusamy; K. Sukumar; A. Raja; S. Saravanan; P. Srinivasan; A. Thangavelu (Archives of Virology, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Molecular typing and pathogenicity assessment of fowl adenovirus associated with inclusion body hepatitis in chicken from India - S. Chitradevi; K. Sukumar; P. Suresh; G. A. Balasubramaniam; D. Kannan (Tropical Animal Health and Production, 2021)

Alteration of root and shoot morphologies by interspecific replacement of individual Upland cotton chromosome or chromosome segment pairs - Mirzakamol S. Ayubov; Tokhir M. Norov; Sukumar Saha; Te-Ming Tseng; K. Raja Reddy; Johnie N. Jenkins; Ibrokhim Y. Abdurakhmonov; David M. Stelly (Euphytica, 2021)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Investigation of Natural Extracts and Sodium Bisulfite Impact on Thermal Signals and Physicochemical Compositions of Litopenaeus vannamei during Chilled Storage - Udayasoorian Lalithapriya; Peter Mariajenita; V. Renuka; Kasirajan Sudharsan; S. Karthikeyan; Meenakshisundaram Sivarajan; D. Murugan; Muthusamy Sukumar (Journal of Aquatic Food Product Technology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Bdnf mRNA splice variants differentially impact CA1 and CA3 dendrite complexity and spine morphology in the hippocampus - Kristen R. Maynard; John W. Hobbs; Mahima Sukumar; Alisha S. Kardian; Dennisse V. Jimenez; Robert J. Schloesser; Keri Martinowich (Brain Structure and Function, 2017)

Multidimensional tree niches in a tropical dry forest - Sandeep Pulla; Hebbalalu S. Suresh; Handanakere S. Dattaraja; Raman Sukumar (Ecology, 2017)
The extent to which interspecific niche differences structure plant communities is highly debated, with extreme viewpoints ranging from fine‐scaled niche partitioning, where every species in the community is specialized to a distinct niche, to neutrality, where species have no niche or fitness differences. However, there exists a default position wherein niches of species in a community are determined by their evolutionary and biogeographic histories, irrespective of other species within the community. According to this viewpoint, a broad range of pair‐wise niche overlaps—from completely overlapping to completely distinct—are expected in any community without the need to invoke interspecific interactions. We develop a method that can test for both habitat associations and niche differences along an arbitrary number of spatial and temporal niche dimensions and apply it to a 24‐yr data set of the eight dominant woody‐plant species (representing 84% and 76% of total community abundance and basal area, respectively) from a 50‐ha permanent plot in a southern Indian tropical dry forest, using edaphic, topographic, and precipitation variables as niche axes. Species separated into two broad groups in niche space—one consisting of three canopy species and the other of a canopy species and four understory species—along axes that corresponded mainly to variation in soil P, Al and a topographic index of wetness. Species within groups tended to have significantly greater niche overlap than expected by chance. Community‐wide niche overlap in spatial and temporal niche axes was never smaller than expected by chance. Species‐habitat associations were neither necessary nor sufficient preconditions for niche differences to be present. Our results suggest that this tropical dry‐forest community consists of several tree species with broadly overlapping niches, and where significant niche differences do exist, they are not readily interpretable as evidence for niche differentiation. We argue, based on a survey of the literature, that many of the observed niche differences in tropical forests are more parsimoniously viewed as autecological differences between species that exist independently of interspecific interactions.

Removal of Cr(VI) using co-immobilized activated carbon and Bacillus subtilis: fixed-bed column study - C. Sukumar; V. Janaki; K. Vijayaraghavan; S. Kamala-Kannan; K. Shanthi (Clean Technologies and Environmental Policy, 2017)

Comparative assessment of genetic diversity in cytoplasmic and nuclear genome of upland cotton - Sharof S. Egamberdiev; Sukumar Saha; Ilkhom Salakhutdinov; Johnie N. Jenkins; Dewayne Deng; Ibrokhim Y. Abdurakhmonov (Genetica, 2016)

Molecular confirmation of Gossypium hirsutum chromosome substitution lines - Sukumar Saha; David M. Stelly; Abdusalom K. Makamov; Mirzakamol S. Ayubov; Dwaine Raska; Osman A. Gutiérrez; Shivapriya Manchali; Johnie N. Jenkins; Dewayne Deng; Ibrokhim Y. Abdurakhmonov (Euphytica, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Mitigation of environmental impacts due to ghat road formation in Palamalai Hills, South India, by optimizing cut and fill volumes using GPS and GIS techniques - R. Arulmozhi; T. Subramani; S. Sukumar (Environmental Monitoring and Assessment, 2015)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Removal of chromium using Rhizobium leguminosarum - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2012)

Endophytic fungal communities in woody perennials of three tropical forest types of the Western Ghats, southern India - T. S. Suryanarayanan; T. S. Murali; N. Thirunavukkarasu; M. B. Govinda Rajulu; G. Venkatesan; R. Sukumar (Biodiversity and Conservation, 2011)

Optimisation of extracellular tannase production from Paecilomyces variotii - N. Raaman; B. Mahendran; C. Jaganathan; S. Sukumar; V. Chandrasekaran (World Journal of Microbiology and Biotechnology, 2010)

Genetic diversity of Macrophomina phaseolina isolates from certain agro-climatic regions of India by using RAPD markers - Bandamaravuri Kishore Babu; S. S. Reddy; Mukesh K. Yadav; M. Sukumar; Vijendra Mishra; A. K. Saxena; Dilip K. Arora (Indian Journal of Microbiology, 2010)

Co-inoculation of the endophytic fungus Piriformospora indica with the phosphate-solubilising bacterium Pseudomonas striata affects population dynamics and plant growth in chickpea - Kamlesh K. Meena; Sukumar Mesapogu; Manish Kumar; Mahesh S. Yandigeri; Geeta Singh; Anil K. Saxena (Biology and Fertility of Soils, 2010)

Tooth Element Levels Indicating Exposure Profiles in Diabetic and Hypertensive Subjects from Mysore, India - G. Nagaraj; A. Sukumar; B. Nandlal; S. Vellaichamy; K. Thanasekaran; A. L. Ramanathan (Biological Trace Element Research, 2009)

Chemical Composition of Major Ions in Rainwater - P. R. Salve; A. Maurya; S. R. Wate; Sukumar Devotta (Bulletin of Environmental Contamination and Toxicology, 2008)

Patterns of tree growth in relation to environmental variability in the tropical dry deciduous forest at Mudumalai, southern India - Cheryl D. Nath; H. S. Dattaraja; H. S. Suresh; N. V. Joshi; R. Sukumar (Journal of Biosciences, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)